Similarities between native and restored forest remnants in hydroelectric reservoir surroundings in Paraná - Lima, Felipe Fiuza de; Ruiz, Emilio Carlos Zilli; Mussio, Carla Fernanda; Dias, Andrea Nogueira; Filho, Afonso Figueiredo; Miskalo, Eneida Martins (Seven Editora, 2024)
Introduction: Due to the demand for the implementation of hydroelectric projects to enrich the Brazilian energy matrix, there is an inevitable need to restore the new Permanent Preservation Areas (APPs) resulting from the formation of the reservoirs of these projects. Objective: The main objective of this study is to evaluate and compare the characteristics of the remaining vegetation formations (middle stage secondary forest) and restored ones (reforested areas) that extend along the margins of the reservoir of the Salto Santiago Hydroelectric Power Plant, located in the municipality of Bonito do Iguaçu River - PR. The purpose of the analysis is to identify variations in the diversity and structure of the studied communities, in addition to defining the stages of succession of the evaluated communities. Methodology: To meet the objective of the study, the analyzes were performed using temporary plots. Three 20x100m plots were installed in the restored areas and 5 plots of 20x100m in the remaining forest. In these plots, all individuals with DBH (diameter at breast height) greater than or equal to 10 cm were measured and identified. Still, smaller plots were allocated to evaluate the regenerating individuals, in which the individuals were identified and counted. Initially, the phytosociological parameters of both communities were estimated and, later, for the analyzes of similarity and indicator species, the plots were divided into subplots of 10x10m, totaling 160 plots. Main Results: In total, 52 species belonging to 25 botanical families were recorded in the remaining areas, compared to 37 species distributed in 17 families in the restored areas. The estimated basal area for the remaining areas was 26.7 m². ha-1, while in the restored areas it was 6.8 m². ha-1. The density of individuals was higher in the remaining areas (904 individuals/ha) in relation to the restored areas (310 individuals/ha). The dominant species were identified as Cupania vernalis in the remaining areas and Mimosa bimocrunata in the restored areas, with the latter being native to the region and frequently used during the restoration process. Conclusion: The results of this study highlighted significant differences between the remaining and restored areas in relation to species composition, density and basal area. The low similarity between communities, as demonstrated by the Jaccard index, does not exclude an overlapping trend as observed in the NMDS analyses. The dominant presence of indicator species suggests promising progress in restoration, while the remaining areas remain in a post-disturbance stage of succession. The research contributes to the understanding of the dynamics of regeneration of plant formations in areas of hydroelectric reservoirs, emphasizing the viability of restoration with species native to the region. DOI:https://doi.org/10.56238/sevened2023.001-004